Information Technology Design For BTN Syariah Mobile Banking Services - Minhatus Saniyah; Hendri Hermawan Adinugraha (ISLAMIC BUSINESS and FINANCE, 2023)
This study aims to dig up information about how to do a SWOT analysis of the BTN Syariah mobile banking application; what the strategies implemented by Bank BTN Syariah in developing BTN Syariah mobile banking application services; how to design a mobile banking application belonging to BTN Syariah. The research method used by researchers is a qualitative type through a case study approach. Then the research subject is the manager of BTN Syariah Pekalongan branch. Retrieval techniques through interviews, observation, and documentation. Data analysis used descriptive analysis by testing the validity of the data using the triangulation method. From the research results, it was found that BTN Syariah responded to the current development of information technology by launching the m-banking application. The m-banking application offered by BTN Syariah has the strength of providing optimal service. The opportunity for this application is to increase m-banking customer service data. The weakness of this application is the lack of features offered, so this can also be a threat, namely, customers may feel bored and choose to use another mobile banking application. Even so, the strategy they implemented to develop this mobile banking service was also felt to have had a very positive effect on increasing the number of users. However, innovation in application service features must be carried out, bearing in mind that currently, many banks have issued mobile banking applications with many feature facilities.